2018
DOI: 10.1007/s10620-018-5175-4
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Correlation Between Gastric and Esophageal Dysmotility Suggests Common Causality

Abstract: The correlation between an abnormal GES and HRM argues for common pathogenic mechanisms of these motility disorders, and possibly common future treatment options. Clinicians should have a high index of suspicion for another motility disorder if one is present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…In Zikos et al's [8] study, the presence of nausea and vomiting was an inverse predictor of an HRM abnormality, a finding consistent with the observation that only 36.9% of the studied cohort had nausea and emesis, in line with observation that relatively more patients with gastric motility disorders experience nausea and emesis in contrast to the more frequently experienced symptoms such as dysphagia and heartburn in patients with esophageal motility disorders.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…In Zikos et al's [8] study, the presence of nausea and vomiting was an inverse predictor of an HRM abnormality, a finding consistent with the observation that only 36.9% of the studied cohort had nausea and emesis, in line with observation that relatively more patients with gastric motility disorders experience nausea and emesis in contrast to the more frequently experienced symptoms such as dysphagia and heartburn in patients with esophageal motility disorders.…”
supporting
confidence: 76%
“…The presence of nausea, gastroesophageal reflux disease (GERD), atypical chest pain, dyspepsia, and dysphagia were not good predictors for an abnormal GES. Dysphagia was a positive predictor for an HRM abnormality, whereas the presence of nausea and vomiting was a negative predictor of HRM abnormality [8].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Potential implications of IEM relate to GERD severity, symptom reporting, and decision making prior to antireflux surgery. Ineffective esophageal motility has a higher prevalence in smooth muscle disorders, such as scleroderma, other connective tissue disorders and gastroparesis, but is not more common in diabetes mellitus, or hypothyroidism . Ineffective esophageal motility has also been reported in Parkinson's disease .…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Several prior studies have shown a significant overlap between dyspeptic and lower gastrointestinal (GI) symptoms, such as constipation and irritable bowel syndrome. [11][12][13] Additionally, prior studies suggest a link between gastroparesis and both esophageal dysmotility 14 and small bowel dysmotility. 15 These relationships suggest that a common pathophysiology may explain symptoms in multiple areas of the GI tract.…”
Section: Introductionmentioning
confidence: 98%